Berlin Declaration on NFDI cross-cutting topics: as agreed on 15.08.2019 - Glöckner, Frank Oliver; Diepenbroek, Michael; Felden, Janine; Overmann, Jörg; Bonn, Aletta; Gemeinholzer, Birgit; Güntsch, Anton; König-Ries, Birgitta; Seeger, Bernhard; Pollex-Krüger, Annette; Fluck, Juliane; Pigeot, Iris; et al. (Zenodo, 2019)
In the spirit of our common interest to build what could become an international beacon for sharing the benefits of high-quality research data and research data management, the signing NFDI consortia strongly support the idea that NFDI must build on a coordinated and inclusive effort fostering the FAIR data principles. Recalling the challenges that interoperability and sharing of data faces, the 21 consortia signing this declaration agreed on a common list of cross-cutting topics.